A pulmonary nodule mislocated in “dorsal” segment due to tri-lobed left lung - Lyu, Xiaohong; Xu, Yuan; Qin, Yingzhi; Ma, Dongjie; Liu, Hongsheng (Frontiers in Surgery, 2023)
Background The left lung has two lobes and one fissure, while the right lung has three lobes and two fissures. Accessory fissures are usually found in imaging examinations and autopsies; however, finding an actual accessory lobe is rare. Case presentation In a lung nodule resection surgery, a 68-year-old male patient was found with three lobes and two fissures in his left lung. The lung nodule was misdiagnosed as being located in the lower lobe because the accessory fissure was misregarded as the oblique fissure. The lung nodule was found in the upper lobe, and this anatomical variation changed the surgical plan. The pathology of the lung nodule was granulomatous inflammation with caseous necrosis with the positive antacid stain. The patient was eventually diagnosed with tuberculosis. Literature review Cases involving the lung accessory fissure and lung accessory lobe variants were reviewed. In 10 autopsy and dissection studies, the incidence of accessory fissure in the left lung was 13.5% (79/587, ranging from 2.7% to 50.0%), and in the right lung, it was 7.3% (42/575, ranging from 3.1% to 30.4%). The incidence of accessory lobes in the left lung was 2.0% (11/547, ranging from 0.0% to 7.4%), and in the right lung was 2.6% (14/539, ranging from 0.0% to 17.4%). The incidence of accessory fissures in bilateral lungs identified by chest x-ray or computed tomography ranged from 7.3% to 32.0%. Three surgical case reports inferred accessory lobes, including a left upper lobectomy, left lung transplantation, and an open thoracotomy. Conclusion This is the first clinical case report that shows that lung accessory lobe caused the mislocation of a lung nodule. Therefore, radiologists and surgeons should be aware of the possibility of an accessory lobe in the lung.